Deweyan Democracy: The Epistemic Context - Jón Olafsson (The University of Akureyri, 2014)
John Dewey famously argued that we should think of democracy as a “way of life”. What this consists in he described as participating according to capacity in public decisions and participating according to need or desire in forming values. He also characterized democracy as “a mode of associated living, of conjoint communicated experience” (Dewey 1966 p. 87; 1954 p. 147; 1957 p. 209). Such and other passages in Dewey’s works show that his conception of democracy is complex. He did not think of it simply as a way of decision-making, nor is democratic procedure of particular importance to him. Concepts such as “associated living” or “communicated experience” point to the social dimensions Dewey was particularly interested in. Dewey also repeatedly claims that democracy demands “social return” from every individual and that democracy enables everyone to develop “distinct capacities” (Dewey 1966, p. 122). A related claim emphasizes how, in a democracy, “all share in useful service and enjoy a worthy leisure” (Dewey 1966, p. 256).